Two-dimensional pseudospherical surfaces with degenerate Bianchi transformation - Gor'kavyi, V. A.; Nevmerzhitskaya, E. N. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We classify two-dimensional pseudospherical surfaces with degenerate Bianchi transformation in a multidimensionalEuclidean space.